Fixed-time observer-based distributed secondary voltage and frequency control of islanded AC microgrids - Mohamed Ghazzali; Mohamed Haloua; Fouad Giri (Institute of Advanced Engineering and Science, 2020)
This paper deals with the problem of voltage and frequency control of distributed generators (DGs) in AC islanded microgrids. The main motivation of this work is to obviate the shortcomings of conventional centralized and distributed control of micro-grids by providing a better alternative control strategy with better control performance than state-of-the art approaches. A distributed secondary control protocol based on a novel fixed-time observer-based feedback control method is designed for fixed-time frequency and voltage reference tracking and disturbance rejection. Compared to the existing secondary microgrid controllers, the proposed control strategy ensures frequency and voltage reference tracking and disturbance rejection before the desired fixed-time despite the microgrid initial conditions, parameters uncertainties and the unknown disturbances. Also, the controllers design and tuning is simple, straightfor-ward and model-free.i.e, the knowledge of the microgrid parameters, topology, loads or transmission lines impedance are not needed in the design procedure. The use of distributed control approach enhances the reliability of the system by making the control system geographically distributed along with the power sources, by using the neighboring DGs informations instead of the DG’s local informations only and by cooperatively rejecting external disturbances and maintaining the frequency and the voltage at their reference values at any point of the microgrid. The efficiency of the proposed approach is verified by comparing its performance in reference tracking and its robustness to load power variations to some of the works in literature that addressed distributed secondary voltage and frequency control.